Academic Motivation of 11th Grade Boarding School Students: The Role of the Pesantren Climate and Self-Efficacy - Ar Rifni, Irfi Widimufti; Fitriah, Elis Anisah; Nurany, Putri Nabhani (Faculty of Psychology, UIN Sunan Gunung Djati, Bandung Indonesia, 2026)
Multiple cognitive load (including formal school, Quran memorization target, organizational activities) combined with a strict 24-hour dormitory schedule can cause academic stress and cognitive overload, thus triggering a decrease in the academic motivation. This study investigates the contribution of the Islamic boarding school climate and self-efficacy to the academic motivation of 11th grade students at Pesantren Persis 76 Tarogong. The method used is a quantitative approach with a multiple linear regression research design. The research involved 94 students selected through a saturated sampling technique. The findings show that the Islamic boarding school climate and self-efficacy simultaneously have a significant effect on academic motivation, with a contribution of 9.7%. These findings emphasize the importance of a supportive school environment and self-efficacy in encouraging students’ motivation to learn.